General anesthesia in children and long-term neurodevelopmental deficits: A systematic review - Xiao, Aoyi; Feng, Yingying; Yu, Shan; Xu, Chunli; Chen, Jianghai; Wang, Tingting; Xiao, Weimin (Frontiers in Molecular Neuroscience, 2022)
Background: Millions of children experienced surgery procedures requiring general anesthesia (GA). Any potential neurodevelopmental risks of pediatric anesthesia can be a serious public health issue. Various animal studies have provided evidence that commonly used GA induced a variety of morphofunctional alterations in the developing brain of juvenile animals. Methods: We conducted a systematic review to provide a brief overview of preclinical studies and summarize the existing clinical studies. Comprehensive literature searches of PubMed, EMBASE, CINAHL, OVID Medline, Web of Science, and the Cochrane Library were conducted by using the relevant search terms ‘general anesthesia’, ‘neurocognitive outcome’ and ‘children’. We included studies investigating children who exposed to single or multiple GA before 18, with long-term neurodevelopment outcomes evaluated after the exposure(s). Results: Seventy-two clinical studies originating from 18 different countries published from 2000 to 2022 are included in this review, most of which are retrospective studies (n = 58). Two-thirds of studies (n = 48) provide evidence of negative neurocognitive effects after GA exposure in children. Neurodevelopmental outcomes are categorized into 6 domains: academics/achievement, cognition, development/behavior, diagnosis, brain studies, and others. Most studies focusing on children less than 7-years detected adverse neurocognitive effect following GA exposure, but not all studies consistently supported the prevailing view that younger children were at greater risk than senior ones. More times and longer duration of exposures to GA, and major surgeries may indicate a higher risk of negative outcomes. Conclusion: Based on current studies, it is necessary to endeavor to limit the duration and numbers of anesthesia and the dose of anesthetic agents. For future studies, we require cohort studies with rich sources of data and appropriate outcome measures, and carefully designed and adequately powered clinical trials testing plausible interventions in relevant patient populations.